Recent Advances in the Synthesis of Bioactive Quinoline-Based 1,2,3-Triazoles via Cu-Catalyzed Huisgen 1,3-Dipolar Cycloaddition (“Click Reaction”) - V. Kouznetsov, Vladimir; Y. Vargas-Mendez, Leonor; I. Zubkov, Fedor (Mini-Reviews in Organic Chemistry, 2016)
Background: Quinoline and 1,2,3-triazoles have attracted increasing attention due to their significant biological activities. Combination of these two scaffolds in one single molecule, quinolinebased 1,2,3-triazoles, gives an excellent opportunity to create new structurally diverse drug-like molecules with potent biological properties. Synthesis of these molecular hybrids has become available from a recently developed copper-catalyzed azide-alkyne cycloaddition methodology. Objective: The aim of the present review is to summarize the recent developments in Cu-catalyzed azide- alkyne cycloaddition reactions for the synthesis of functionalized quinoline-based 1,2,3-triazoles. Method: The discussion was organized according to structural criteria and functional role of the triazole ring connected to quinoline derivatives. The quinoline-based 1,2,3-triazoles obtained through azidealkyne cycloaddition methodology were classified in two general groups: quinoline-based triazoles, in which 1,2,3-triazole ring acts as pharmacophore and triazoles containing quinoline and other heterocycles, in which 1,2,3-triazole ring acts as linker. Both of these groups are based on triazole structures of type 1 (1-(quinolinyl)-1,2,3-triazoles) and type 2 (4-(quinolinyl)-1,2,3-triazoles). Results: Recent studies (112 references) on the functionalization of quinoline derivatives by 1,2,3- triazole incorporation have been discussed providing reaction conditions of organoazides and alkyne derivatives and biological activity of the obtained quinoline-based 1,2,3-triazoles. Additionally, various recent advancements in the synthetic aspects of the copper-catalyzed azide-alkyne cycloaddition have been briefly analyzed. Conclusion: This information should furnish a fresh insight for organic chemists in the design of novel bioactive molecules that contain the triazole and quinoline skeletons. It can be expected that efficient, original preparative methods for new biological materials based on quinoline-triazole structures will be reported in the near future.
Keywords: 2